2021
DOI: 10.1186/s12911-021-01565-z
|View full text |Cite|
|
Sign up to set email alerts
|

Supporting the classification of patients in public hospitals in Chile by designing, deploying and validating a system based on natural language processing

Abstract: Background In Chile, a patient needing a specialty consultation or surgery has to first be referred by a general practitioner, then placed on a waiting list. The Explicit Health Guarantees (GES in Spanish) ensures, by law, the maximum time to solve 85 health problems. Usually, a health professional manually verifies if each referral, written in natural language, corresponds or not to a GES-covered disease. An error in this classification is catastrophic for patients, as it puts them on a non-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Our group has experience using static word embeddings for patient classification deployed in a hospital (Villena et al, 2021b ) and using stacked embeddings that combine both static and contextualized embeddings for named entity recognition (Báez et al, 2020 ; Báez et al, 2022 ) and automatic coding (Villena et al, 2021a ). Evaluating the automatic translation of clinical sentences has pointed us the need for creating reliable intrinsic tests created from scratch for the Spanish language, which can be valuable for both static and contextual word embeddings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group has experience using static word embeddings for patient classification deployed in a hospital (Villena et al, 2021b ) and using stacked embeddings that combine both static and contextualized embeddings for named entity recognition (Báez et al, 2020 ; Báez et al, 2022 ) and automatic coding (Villena et al, 2021a ). Evaluating the automatic translation of clinical sentences has pointed us the need for creating reliable intrinsic tests created from scratch for the Spanish language, which can be valuable for both static and contextual word embeddings.…”
Section: Discussionmentioning
confidence: 99%
“…These referrals were obtained via Chilean Transparency Law, a government-wide initiative giving every citizen the right to request anonymized public data (Martinez et al, 2019 ). We got access to 11,826,843 referrals collected by the authors (Villena et al, 2021b ), and a subset of this corpus has been annotated with entities and relations clinically relevant 4 . These diagnostic suspicions were written directly by general practitioners in a primary-care setting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1186/ s12911-021-01565-z. *Correspondence: jdunstan@uchile.cl 1 Center for Mathematical Modeling -CNRS UMI2807, Faculty of Physical and Mathematical Sciences, University of Chile, Santiago, Chile Full list of author information is available at the end of the article…”
Section: Publisher's Notementioning
confidence: 99%
“…Following publication of the original article [ 1 ], it was reported that the list of authors was published in the incorrect order. Jocelyn Dunstan was erroneously listed as the first author instead of the last.…”
Section: Correction To: Bmc Med Inform Decis Mak 21:208 (2021) 101186/s12911-021-01565-zmentioning
confidence: 99%